The Impact of Value Added Tax on Private Investment in Nigeria - Adejare, Adegbite, Tajudeen; Akande, Shittu Saheed (Account and Financial Management Journal, 2017)
The study examined the impact of value added tax on private investment in Nigeria. Data were obtained from CBN statistical Bulletin from 1994 to 2015. Pearson product moment correlation and multiple regressions were employed to analyze the relationship between the dependent variable (Private Investment) and independent variables (Value Added tax, interest rate, inflation rate and exchange rate.). Findings show that there is a positive significant relationship between Private Investment and the Value Added tax, interest rate, inflation rate and exchange rate with the adjusted R2 @ 75%. Therefore, Value Added tax, interest rate, and exchange rate have strong and positive statistical impact on Private Investment in Nigeria. It is now recommended that government should increase the rate of value added tax in Nigeria so that the funds realized from value added tax will be expended on the provision of social and infrastructural facilities which ultimately will boost the economy by way of enhance the level of investment ( encourage investors) which invariably create employment opportunity in the country.